Benefits of bandwidth feedback in learning a complex gymnastic skill - Sadowski, J.; Mastalerz, A.; Niznikowski, T. (Journal of Human Kinetics, 2013)
The aim of this study was to examine the effects of two different frequencies of feedback during the process of learning a complex gymnastic skill, the round-off salto backward tucked. Thirty male acrobats participated in the study. They were randomly assigned to two groups: B - bandwidth feedback (n=15) or C - 100% feedback (n=15). Group B was provided with error information regarding the key elements of movement techniques only (bandwidth feedback). Our research demonstrates the advantage of augmented feedback information related to errors in the key elements. Information about errors in the key elements during learning a complex gymnastic skill prevents the gymnast from becoming overwhelmed, which promotes better motor control. These results provide support for the generalisation of bandwidth feedback principles to a complex task. Our research shows that the guidance hypothesis can also be tested in practical settings for a complex movement task.